Monetary Policy in an Emerging European Economic and Monetary Union : Key Issues - Frenkel, Jacob; Goldstein, Morris (Washington, D.C. : International Monetary Fund, 1990)
This paper discusses key issues relating to the design and implementation of monetary policy in an emerging European economic and monetary union. Specific institutional proposals for transition to EMU are neither endorsed nor dismissed. In examining the goals of monetary policy, the paper explores the interrelationships among price stability, current account equilibrium, and exchange rate stability. Turning to the implementation of monetary policy, the issues addressed are: coordination versus autonomy, rules versus discretion, and the role of sterilized official intervention. Finally, the last part of the paper emphasizes the importance of fiscal discipline, and evaluates several alternative mechanisms for encouraging it.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet